A 640×512 ROIC with optimized BDI input stage and low power output buffer for CQDs-based infrared image sensor. (June 2022) - Li, Hao; Hu, Ang; Nie, Zheng; Liu, Dongsheng; Niu, Guangda; Gao, Liang; Tang, Jiang
Abstract: A 640 × 512 readout integrated circuit (ROIC) for colloidal quantum dots (CQDs) infrared image sensor is presented in this paper. An optimized buffered direct injection (BDI) pixel circuit and a low power rail-to-rail output buffer are proposed to achieve higher array-level consistency of output voltage. The ROIC can process photocurrent of CQDs detector from 100 fA to 100 pA with a conversion gain (CG) of 2.13μV/e −, full well capacity (FWC) of 4.6 × 10 5 e − and readout noise of 100e − . With 1.8 V power supply for both digital and analog modules, the output signal swing exceeds 1 V and performs linearity over 99.95% under different PVT conditions. The ROIC is designed and simulated with SMIC 0.18 μm mixed-signal 1-poly 6-metal (1P6M) process and the die size is 11.13 mm × 8.78 mm.